Lip balm using cinnamon oleoresin and essential oil: microbiological safety assessment with accelerated and extended stability (Research, Society and Development, 2020)
Due to the growth of the cosmetics industry, developments and improvements are needed for the productive sector and its products to meet consumer demand and the quality standards imposed by inspection bodies. As a result, an area has developed to meet these needs that is known as phytocosmetics. This area involves the inclusion of constituents with of plant origin in the cosmetic product formulation. The objective of this work was to compare the formulations of lip moisturizers incorporating oleoresins and essential oils of cinnamon (Cinnamomun verum), in addition to testing the microbiological safety and the Accelerated and Extended Stability of the formulated products. The tests revealed that the proposed formulations are microbiologically stable and safe, which is due to the antimicrobial activity of the oleoresin and cinnamon essential oil used in the formulations.